Emerging seaweed extraction techniques using ionic liquids - Martins, Margarida (2021)
In the last few decades, interest in primary and secondary metabolites from seaweeds has increased due to their high potential in important fields such as pharmaceuticals and cosmetics. In this context, the development of processes of extraction and purification that overcome the principal disadvantages of conventional methodologies is of utmost importance. Ionic liquids (ILs) have emerged as an alternative class of solvents in the extraction of compounds from a biomass. In this chapter, literature addressing the use of ILs in studies of extraction, purification, and biomass dissolution regarding seaweeds will be analyzed and discussed.